The Effect of Fermented Aflatoxins Contaminated Feed on Digestibility and Performance of Broiler Chickens - Isabelle Beatrice Mukandungutse; James K Tuitoek; Anthony M King’ori; Meshack A Obonyo (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2020)
Poultry is susceptible to mycotoxicoses caused by aflatoxins. Two experiments were carried out, where twenty-four, 28days old and 144 one-day-old broilers were assigned to six diets respectively. The diets were: diet1 (no aflatoxin and not fermented), diet2 (no aflatoxin and fermented without yeast), diet3 (no aflatoxin and fermented with yeast), diet4 (contained aflatoxin and not fermented), diet5 (contained aflatoxin and fermented without yeast) and diet6 (contained aflatoxin fermented with yeast). The aflatoxins were 20.034 and 30.08ppb for the first and second experiments respectively. In the first experiment, each diet was assigned to 4 chickens for 7days adaptation and 7days for feces and leftover collection. The feces were oven dried for the determination of dry matter digestibility (DMD), metabolizable energy (ME) and nitrogen (MN). In the second experiment, each diet was assigned to six chicks, replicated 4 times for 21days. Leftovers and mortalities were recorded daily and chicks were weighed on a weekly basis. The results showed that DMD and MN were significantly (p<0.05) affected by fermentation. Natural fermentation improved DMD of the clean and contaminated diets. No difference found in feed intake and body weight gain. However, gain: feed ratio was significantly (p=0.048) better in broilers fed diets fermented naturally. The mortality rate was 75.0% in chicks fed on aflatoxin diet which was not fermented. Therefore, natural fermentation is the best method of improving the quality of aflatoxin contaminated feed for broilers.